Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.1 Definition of the Derivative - Exercises - Page 103: 17



Work Step by Step

$f'(x)=\lim\limits_{h \to 0}\frac{f(x+h)-f(x)}{h}=\lim\limits_{h \to 0}\frac{[7(x+h)-9]-(7x-9)}{h}$ $=\lim\limits_{h \to 0}\frac{7x+7h-9-7x+9}{h}=\lim\limits_{h \to 0}(7)=7$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.